VD_FINDINFO HC / 2014 / 779 vom 6. Oktober 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, FRAIS JUDICIAIRES, TRANSACTION JUDICIAIRE, PROTECTION DE L'ENFANT | 26a LProMin, 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)